Possible underestimation by sports medicine of the effects of early physical exercise practice on the prevention of diseases in adulthood - Fernandes, Romulo Araujo [UNESP]; Coelho-E-Silva, Manuel João; Lima, Manoel Carlos Spiguel; Cayres, Suziane Ungari; Codogno, Jamile Sanches; Lira, Fábio Santos (Bentham Science Publishers, 2015)
In modern society, combatting cardiovascular and metabolic diseases has been highlighted as an urgent global challenge. In recent decades, the scientific literature has identified that behavioral variables (e.g. smoking, unhealthy diet and physical inactivity) are related to the development of these outcomes and, therefore, preventive actions should focus on the promotion of physical exercise practice and a healthy diet, as well as combatting the smoking habit from an early age. The promotion of physical exercise in the general population has been suggested as a relevant goal by significant health organizations around the world. On the other hand, recent literature has indicated that physical exercise performed in early life prevents the development of diabetes mellitus, dyslipidemia and arterial hypertension during adulthood, although this protective effect seems to be independent of the physical activity performed during adulthood. Apparently, the interaction between physical exercise and human growth in early life constitutes an issue which is not completely understood by sports medicine. The aim of the present review was therefore to discuss recent evidence on the effects of physical exercise performed during childhood and adolescence on cardiovascular and metabolic outcomes in adulthood.
Keywords: Inflammation; Diabetes mellitus; Physical activity; Epidemiology; Adolescents; Genetics